Conservative treatment of periprosthetic femur fractures around metaphyseal short stems – A feasible option?. (June 2017) - Toth, K.; Gality, H.; Gion, K.; Sisak, K.
Abstract: Periprosthetic femoral fractures are rare but significant events following total hip replacement. Metaphyseal short stems have recently been popularized as a bone preserving alternative to conventional uncemented total hip replacement. We present two periprosthetic femur fractures which occurred around two different metaphyseal uncemented stem designs. Successful conservative treatment was possible in both cases achieving bony union and excellent clinical results.